Value-sharing problem for p-adic meromorphic functions and their difference operators and difference polynomials - An, Vu Hoai; Khoai, Ha Huy (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We discuss the value-sharing problem, versions of the Hayman conjecture, and the uniqueness problem for p-adic meromorphic functions and their difference operators and difference polynomials.